Extending Bianchi’s classification of homogeneous three-spaces - Abdullah, Aslam; Zainuddin, Hishamuddin; Hassan, Zainul Abidin (2005)
We discuss the extensions of a few of the Bianchi types of homogeneous cosmologies described by three-parameter isometry groups G3 with transitive action on three-spaces to those involving four-parameter transitive groups G4 of isometries of four-spaces. By extending a three-space line element, which admits the Bianchi type-N (N=I,II,V,IX) to that of four-space, we seek for G4.